VOCABULARY LEARNING STRATEGIES EMPLOYED BY UNDERGRADUATE INDONESIAN EFL STUDENTS - Fitria Wulan Sari (Universitas Khairun, 2021)
Vocabulary is crucial in all language acquisitions, whether the first language, second language or foreign language. Due to the importance of vocabulary, a comprehensive language learning strategy is needed. The present study investigates the various vocabulary learning strategies used by undergraduate Indonesian students majoring English Language Education Study Programin learning new words. Descriptive qualitative was applied as a research method to find out the objective of the research. The techniques of data collection used in this research were observation and questionnaire. The data analysis used in this research was the interactive model analysis from Miles and Huberman that consists of data reduction, data display, and conclusion. The results showed that there were seventeen strategies used by the students in learning vocabulary.Â